Answer: 58.666666666667
Step-by-step explanation:
my brain
M5 minus M6 will get M1
So 62 - 38 = 24
24 x 3 = 72
So M3 is 72
<span>5x^2 + 5y^2 + 10x − y = 0 it is the same of </span>
<span>x^2 + y^2 + 2x −1/5y = 0
and then </span>
(x + 1)^2 - 1+ (<span><span>y−1/10)^2 -1/100=0
</span> </span>(x + 1)^2 + (<span>y −1/10)^2 =(101/100)
the center is C(-1, 1/10), and the radius is R= sqrt(101)/10
</span>
Step-by-step explanation:
Q9. 5n + 8 = 43
5n = 43 - 8
5n = 35
n = 35/5
n = 7
Q10. y/6 - 7 = 4
y/6 = 4 + 7
y/6 = 11
y = 11×6
y = 66
Q11. 8w - 15 = 57
8w = 57 + 15
8w = 72
w = 72/8
w = 9
Q12. g/3 + 11 = 25
g/3 = 25 - 11
g/3 = 14
g = 14×3
g = 42
Q13. f/5 - 22 = -25
f/5 = -25 + 22
f/5 = -3
f = -3×5
f = -15
Q14. -4p + 19 = 11
4p = 19 - 11
4p = 8
p = 8/4
p= 2